Host plant resistance to Diatraea spp. attack (Lepidoptera: Crambidae) in sugarcane. (2017)
The sugarcane stem borers Diatraea spp. are the most important sugarcane pests in Colombia. In the country the production of varieties does not involve selection for insect resistance, but in the final stage of selection evaluations are made on the percent of bored internodes (Infestation Intensity) and an Injury Rating is given according to the injury mean in each trial, that after at least three trials produces a mean injury rating known as Resistance Index (R.I.). This work was directed to identify genotypes in relation to its resistance characterization, this on three localities and under conditions of two crop cycles (plant-cane and first ratoon). By means of a contingency table, analysis of the frequency of the Injury Rating were done in 16 cultivars, and a statistical analysis of the Proportion of Bored Internodes and the R. I. were developed. Consistently the cultivars that exhibit environmental and phenological stability are CC 93-3826 and CC 93-3803 were graded as susceptible, whereas CC 93-3811 as resistance and CC 93-3895 as moderately resistant. These cultivars with characterization of contrasting resistance will be used as checks in trials under controlled conditions to characterize host plant resistance in a more precise way, avoiding environmental variation in the determination of the resistance against the sugarcane stem borers.